FEATURE FILM AS A MEDIA EDUCATION TECHNOLOGY IN ENGLISH LANGUAGE LESSONS (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This paper discusses how feature films can be used as a media education technology in English language lessons, especially with learners at the middle and upper-secondary stage (approximately CEFR A2–B2). Films offer rich, multimodal input: learners do not rely only on words, but also on facial expressions, gestures, setting, and tone of voice. Because of this, films can support comprehension, motivation, and communicative practice. However, film-based lessons often fail when teachers either turn the classroom into a cinema or reduce the work to translation and vocabulary lists. To avoid these extremes, the paper proposes a practical classroom framework: selecting short scenes with clear communicative value, defining a specific speaking goal (e.g., requesting clarification, negotiating, persuading), using a staged task sequence (pre–while–post), and assessing performance with simple, transparent criteria. A sample lesson model is provided to demonstrate how film scenes can develop listening skills, pragmatic competence, fluency through chunks, and interactive speaking. The paper argues that films become most effective when they function not as entertainment, but as structured media texts that help learners interpret meaning and communicate it in realistic contexts.